2016
DOI: 10.1016/j.cger.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pain on Family Members and Caregivers of Geriatric Patients

Abstract: SYNOPSIS This article provides an overview of the literature describing the effects of geriatric patients’ pain on family members’ relationships, psychological well-being, and physical health. The theoretical mechanisms that underlie the association between patients’ pain and family members’ outcomes are outlined, and studies describing these mechanisms are summarized. Limitations to the current literature are discussed, and key recommendations for future research and practice are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 82 publications
0
17
0
Order By: Relevance
“…Pain is associated with poor quality of life (Snow et al, 2009; Torvik et al, 2010), emotional disturbance (Bair et al, 2003; Boakye et al, 2016), social withdrawal (Mellado et al, 2016; Smith, 2017), sleep impairments (Boakye et al, 2016), and increased health service use (Gaskin & Richard, 2012). Its effects extend beyond the individual, exacting a toll on family relationships (Riffin et al, 2016; West et al, 2012) and on caregivers’ physical and emotional well-being (Martire et al, 2019; Nah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Pain is associated with poor quality of life (Snow et al, 2009; Torvik et al, 2010), emotional disturbance (Bair et al, 2003; Boakye et al, 2016), social withdrawal (Mellado et al, 2016; Smith, 2017), sleep impairments (Boakye et al, 2016), and increased health service use (Gaskin & Richard, 2012). Its effects extend beyond the individual, exacting a toll on family relationships (Riffin et al, 2016; West et al, 2012) and on caregivers’ physical and emotional well-being (Martire et al, 2019; Nah et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…As research has repeatedly shown [ 47 – 51 ], the expression of chronic pain often has a negative impact on family members, especially if they do not know what information to retain or how to react to it. Nevertheless, even if chronic pain often has a deleterious effect on familial relationships [ 52 ], talking about it with specific family members can be an opportunity to strengthen interpersonal relations [ 53 ] and to find social support to live with chronic pain in everyday life [ 54 ]. The selection of specific interlocutors leads to a division of labor in the social network [ 55 ]: the communication about chronic pain with direct relatives is usually motivated both by their ability to provide practical help and to be emotionally supportive.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, husbands’ pain could lead to marital problems that heighten wives’ psychological distress. Pain behaviors are reciprocally related to aversive spousal interactions, which can result in marital conflict, diminished emotional closeness and intimacy, and the eventual erosion of partner support [37,60]. People with severe pain also commonly withdraw from their marriage and other important social ties in ways that may strain these relationships and amplify the emotional consequences of pain [73].…”
Section: Discussionmentioning
confidence: 99%